BDNF Val66Met polymorphism and lithium response: a meta-analysis. (November 2013) - Ehret, Megan J; Baker, William; O'Neill, Hannah
Aim: To characterize the impact of the Val66Met polymorphism on lithium response in patients with bipolar disorder.Methods: A systematic literature search of MEDLINE, Web of Science, PsychINFO and Cochrane CENTRAL was conducted from the earliest possible date through to 1 July 2012. The search was performed using the following medical subject headings: bipolar disorder, lithium, lithium carbonate, pharmacogenomics, pharmacogenetics, polymorphism and brain-derived neurotrophic factor. Five of 71 identified studies met the inclusion criteria. Data were abstracted using a standardized data abstraction tool. For categorical end points, the pooled odds ratio with 95% CI was calculated. Random effects models were used for analysis.Results: The Val66Met polymorphism did not predict response to prophylactic lithium in this combined population (odds ratio: 2.67; p = 0.078). Conclusion: This analysis suggests that the Val66Met polymorphism does not predict response to lithium treatment in bipolar disorder in this combined population. Prospective studies are needed to clearly define the role of Val66Met polymorphism of BDNF in lithium response.